Methodology of discussion clubs organization in English for students - Axmadullina , Alina (The Lingua Spectrum, 2024)
In the context of globalization and integration, English has become a key tool for communication and information exchange, highlighting the need to enhance students' language proficiency. One effective method to achieve this is through the organization of discussion clubs, where students can develop their speaking skills, critical thinking, and cultural awareness. This paper examines a methodological approach to organizing discussion clubs, including topic selection, discussion formats, and motivation techniques. Special attention is given to creating an atmosphere of trust and mutual respect, which encourages students to feel more comfortable and actively participate in discussions.